Financial Governance, Digital Economy and Efficiency in Audit Processes: A Multidimensional Analysis in the Context of Brexit, Bitcoin, SMEs and Audit Systems - Azari, Shirin; Taheri, Roya (International Journal of Business Management and Entrepreneurship, 2025)
This study offers a multidimensional investigation into the intersection of financial governance, the digital economy, and audit efficiency, contextualized by key global developments such as Brexit, the rise of Bitcoin, and the evolving role of SMEs in technological adoption. Employing a qualitative methodology based on document analysis, case studies, and expert interviews, the research analyzes institutional, organizational, and technological layers that shape digital audit processes. Findings demonstrate that post-Brexit regulatory divergence has complicated audit standard harmonization, particularly for SMEs engaged in cross-border trade. The digital economy exemplified by blockchain, AI, and automated compliance tools has enhanced transparency and efficiency in auditing but also introduced new risks such as cybersecurity threats and regulatory lag. SMEs show increased audit performance when supported by hybrid digital governance models, yet continue to face adoption barriers due to limited financial and technological resources. The study concludes that digital transformation in audit systems is a strategic necessity rather than a technological option. It calls for globally aligned yet locally adaptive regulatory frameworks, increased SME support mechanisms, and robust governance models capable of monitoring emerging risks. These insights offer valuable guidance for policymakers, audit professionals, and scholars in designing resilient, inclusive, and efficient digital audit infrastructures